Multiple voices in academic and professional discourse : current issues in specialised language research, teaching and new technologies - Maruenda-Bataller, Sergio; Clavel-Arroitia, Begoña (Cambridge Scholars Publishing, 2011)
The demands of today's society for greater specialization have brought about a profound transformation in the humanities, which are not immune to the competitive pressure to meet new challenges that are present in other sectors. Thus, lecturers and researchers in modern languages and applied linguistics departments have made great efforts to design syllabi and materials more attuned to the competences and requirements of potential working environments. At the same time, linguists have attempt ...